Endogenous ownership structure: Factors affecting the post-privatisation equity in largest Hungarian firms - Kate Bishop; Igor Filatotchev; Tomasz Mickiewicz (Fondazione Eni Enrico Mattei (FEEM), 2002)
Using a data set for 162 largest Hungarian firms during the period of 1994-1999 this paper explores the determinants of equity shares held by both foreign investors and by Hungarian corporations. We find evidence of a post-privatisation evolution towards more homogeneous equity structures, where dominant categories of owners aim at achieving controlling stakes. Here, the foreign investors and Hungarian corporations play the major role. In addition, focusing on firm level characteristics we find that the exporting firms attract foreign owners, who acquire controlling equity stakes. Similarly, the firm size measurements are positively associated with the presence of foreign investors. However, they are negatively associated with 100% foreign ownership, possibly because the marginal costs of acquiring additional equity are growing with the size of the assets. We interpret the results in light of the existing theory. In particular, following Demsetz and Lehn (1985) and Demsetz and Villalonga (2001) we argue that equity should not be treated as an exogenous variable. As for specific determinants of equity levels, we focus on informational asymmetries and (unobserved) ownership specific characteristics of foreign investors and Hungarian investors.
Keywords: G32; G34; P31; 330; Ownership structure; corporate control; foreign investors; privatisation; Eigentümerstruktur; Corporate Governance; Aktiengesellschaft; Großunternehmen; Ungarn